Effect of Chemically synthesis compared to biosynthesized zinc oxide nanoparticles using extract of Vitex agnus on the expression of MexAB-OprM efflux pump genes of Multi-Drug Resistance Pseudomonas aeruginosa (Baghdad Science Journal, 2024)
The current study's goal was to find out how the expression of the efflux pump genes (MexAB-OprM) in MDR P. aeruginosa isolates was influenced by chemically manufactured Zinc Oxide Nanoparticles  using sol-gel method as compared to biosynthesized Zinc Oxide Nanoparticles  using Vitex agnus-castus leaves extract. PCR analysis was used to  confirmthe  the presence of 16S rRNA gene in all 16 P. aeruginosa isolates The findings indicated that P. aeruginosa tested positive for 16S rRNA (100%), and 7 (43.75%) of the isolates were MDR. All MDR isolates carried MexA, MexB and OprM genes.The Vitex extract's GC-MS analysis exposed the existence of active chemicals. The size of the synthesized Zinc Oxide Nanoparticles ranged from 22 to 74 nm. The Minimum inhibitory concentration values for chemically synthesized NPs, biosynthesized NPs, and Vitex extract against concentrations  were 1024, 256, and 512 μg/mL, respectively, when tested against MDR isolates. Biosynthesized Zinc Oxide Nanoparticles have a greater inhibitory effect on efflux pump genes than chemically synthesized Zinc Oxide Nanoparticles and Vitex extract in the expression of MexA, MexB, and OprM genes in samples treated with sub MIC of Zinc Oxide Nanoparticles and plant extract compared to non-treated samples. One way that nanoparticles work against bacteria is by suppressing the expression of the efflux pump genes, which lowers the number of active efflux pumps on the cell surface. As a result, Zinc Oxide Nanoparticles are regarded by the pharmaceutical sector as a potential medicinal option